Financial Burden in Blood or Marrow Transplantation Survivors During the COVID-19 Pandemic: A BMTSS Report. Issue 5 (10th February 2023) - Bhatia, Smita; Dai, Chen; Hageman, Lindsey; Wu, Jessica; Schlichting, Elizabeth; Siler, Arianna; Funk, Erin; Hicks, Jessica; Lim, Shawn; Balas, Nora; Bosworth, Alysia; Te, Hok Sreng; et al.
Abstract : PURPOSE: The financial burden experienced by blood or marrow transplant (BMT) survivors during the COVID-19 pandemic remains unstudied. We evaluated the risk for high out-of-pocket medical costs and associated financial burden experienced by BMT survivors and a sibling comparison group during the COVID-19 pandemic. METHODS: This study included 2, 370 BMT survivors and 750 siblings who completed the BMT Survivor Study survey during the pandemic. Participants reported employment status, out-of-pocket medical costs, and financial burden. Medical expenses ≥ 10% of the annual household income constituted high out-of-pocket medical costs. Logistic regression identified factors associated with high out-of-pocket medical costs and financial burden. RESULTS: BMT survivors were more likely to incur high out-of-pocket medical costs (11.3% v 3.1%; adjusted odds ratio [aOR], 2.88; 95% CI, 1.84 to 4.50) than the siblings. Survivor characteristics associated with high out-of-pocket medical costs included younger age at study (aORper_year_younger_age, 1.02; 95% CI, 1.00 to 1.03), lower prepandemic annual household income and/or education (< $50, 000 US dollars and/or < college graduate: aOR, 1.96; 95% CI, 1.42 to 2.69; reference: ≥ $50, 000 in US dollars and ≥ college graduate), > 1 chronic health condition (aOR, 2.82; 95% CI, 2.00 to 3.98), ≥ 1 hospitalization during the pandemic (aOR, 2.11; 95% CI, 1.53 to 2.89), and being unemployed during the pandemic (aOR, 1.52; 95% CI, 1.06 to 2.17). Among BMT survivors, high out-of-pocket medical costs were significantly associated with problems in paying medical bills (aOR, 10.57; 95% CI, 7.39 to 15.11), deferring medical care (aOR, 4.93; 95% CI, 3.71 to 6.55), taking a smaller dose of medication than prescribed (aOR, 4.99; 95% CI, 3.23 to 7.70), and considering filing for bankruptcy (aOR, 3.80; 95% CI, 2.14 to 6.73). CONCLUSION: BMT survivors report high out-of-pocket medical costs, which jeopardizes their health care and may affect health outcomes. Policies aimed at reducing financial burden in BMT survivors, such as expanding access to patient assistance programs, may mitigate the negative health consequences.